The Changing National Health Service: Market-Based Reform and Morality; Comment on "Morality and Markets in the NHS" - Lucy Frith (Kerman University of Medical Sciences, 2015)
This commentary explores some of the issues raised by Gilbert et al.short communication, Morality and Markets in the NHS. The increasing role of market mechanisms and the changing types of healthcare providers together with the use of choice and competition to drive improvements in quality in the National Health Service (NHS), all have important ethical implications. In order for the NHS to continue providing the level of service quality that out performs many high-income countries, despite spending much less on healthcare, we need a re-think of creeping marketization and privatisation and a consolidation of the NHS as a publically owned resource run for the benefit of patients and the public, not commercial interests.